2015
DOI: 10.1049/iet-pel.2014.0428
|View full text |Cite
|
Sign up to set email alerts
|

Reliable transformerless battery energy storage systems based on cascade dual‐boost/buck converters

Abstract: In this study, the cascade dual-boost/buck half-bridge and full-bridge bidirectional ac-dc converters are proposed for grid-tie transformerless battery energy storage systems (BESSs). The proposed converter contains the advantages of the traditional cascade H-bridge (CHB) converter. However, compared with CHB converter, there is no shoot-through issue in the proposed converter, which is more reliable for BESS. In addition, a unified control scheme is proposed for active-power control and individual state-of-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Various PWM techniques are employed by researchers on MLC based BSSs. However, the most popular one is phase-shifted PWM (PS-PWM) method as it is extensively utilised in MMCs [67,83,164,165,167,169,170,172,173,[197][198][199][200] and CSM-MLCs [38,65,119,122,123,159,175,177,180,186,194,[201][202][203][204][205]. In PS-PWM, carriers of subsequent SMs are shifted in phase and phase-shift angle is determined by the number of SMs.…”
Section: Pulse Width Modulationmentioning
confidence: 99%
“…Various PWM techniques are employed by researchers on MLC based BSSs. However, the most popular one is phase-shifted PWM (PS-PWM) method as it is extensively utilised in MMCs [67,83,164,165,167,169,170,172,173,[197][198][199][200] and CSM-MLCs [38,65,119,122,123,159,175,177,180,186,194,[201][202][203][204][205]. In PS-PWM, carriers of subsequent SMs are shifted in phase and phase-shift angle is determined by the number of SMs.…”
Section: Pulse Width Modulationmentioning
confidence: 99%
“…Simulation tests of PET with two seven-level CHB inverters (eighteen H-bridges), nine DABs and nine MF transformers are time-consuming, especially due to the high number of switching U HB = γ ¢ U C , (10) I HB = γ ¢ I, (12) where: U o -the output voltage of a single H-bridge.…”
Section: The Matlab-simulink Model Of Chb Convertermentioning
confidence: 99%
“…Thus it has also been demonstrated that multilevel converters can not only perform essential string balancing operations, but also adapt to battery strings as they degrade, reducing the barriers to use of already degraded batteries such as second life electric vehicle batteries. An aspect consistent across papers published in the field, is the lack of justification for the number of levels chosen in their analyses [2,3,6,7]. While this is not a criticism of the research, and certainly does not invalidate their efforts, some sort of analytical method for evaluating multilevel converters of increasing order would be of use in moving this technology from research into industrial application.…”
Section: Introductionmentioning
confidence: 98%